Higher human CD4 T cell response to novel Mycobacterium Tuberculosis Latency associated Antigens Rv2660 and Rv2659 in Latent Infection compared with Tuberculosis Disease - Govender, Lerisa; Scriba, Thomas J.; Kagina, Benjamin M.N.; Rosenkrands, Ida; Mahomed, Hassan (Vaccine, 2010)
One third of the world's population is infected with Mycobacterium tuberculosis (M.tb). A vaccine that would prevent progression to TB disease will have a dramatic impact on the global TB burden. We propose that antigens of M.tb that are preferentially expressed during latent infection will be excellent candidates for post-exposure vaccination. We therefore assessed human T cell recognition of two such antigens, Rv2660 and Rv2659. Expression of these was shown to be associated with non-replicating persistence in vitro. After six days incubation of PBMC from persons with latent tuberculosis infection (LTBI) and tuberculosis (TB) disease, Rv2660 and Rv2659 induced IFN-γ production in a greater proportion of persons with LTBI, compared with TB diseased patients. Persons with LTBI also had increased numbers of viable T cells, and greater specific CD4+ T cell proliferation and cytokine expression capacity. Persons with LTBI preferentially recognize Rv2659 and Rv2660, compared with patients with TB disease. These results suggest promise of these antigens for incorporation into post-exposure TB vaccines.
Keywords: Mycobacterium tuberculosis; TB disease; Post-infection vaccine; Latency antigens